2020
DOI: 10.4236/ojog.2020.1090118
|View full text |Cite
|
Sign up to set email alerts
|

Materno-Fetal Outcomes of COVID-19 Infected Pregnant Women Managed at the Douala Gyneco-Obstetric and Pediatric Hospital—Cameroon

Abstract: Introduction: The first case of the novel coronavirus (COVID-19) pandemic in Cameroon was confirmed on March 6, 2020. Though widely considered that pregnant women are more susceptible to respiratory tract infections, the available body of literature on the effect of COVID-19 on pregnancy outcomes is shy from being conclusive. In Cameroon, the Douala Gyneco-Obstetric and Pediatric Hospital (DGOPH) was one of the main frontline tertiary health facilities for the management of severe forms of the disease. After f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 10 publications
3
9
0
Order By: Relevance
“…These results are consistent with those found in two cohort studies conducted by Knight et al in the UK and Zaigham et al in Sweden [4] [14]. However, they differ from those found in Senegal by Diouf et al who reported headache as the main symptom [12]. Patients with elevated D-dimer, LDH, PT and aPTT were all between the moderate and severe phases of the disease.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…These results are consistent with those found in two cohort studies conducted by Knight et al in the UK and Zaigham et al in Sweden [4] [14]. However, they differ from those found in Senegal by Diouf et al who reported headache as the main symptom [12]. Patients with elevated D-dimer, LDH, PT and aPTT were all between the moderate and severe phases of the disease.…”
Section: Discussionsupporting
confidence: 91%
“…We found that 92.7% (89) of cases were singleton pregnancies and 56.25% (54) infected pregnant women were in the third trimester of pregnancy at the time of diagnosis. These results are similar with most available data which demonstrate that pregnant women are mostly diagnosed in the third trimester of pregnancy [12] [13]. Li et al in China in 2020 found 88.2% of monofetal pregnancies [13].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In a small observational cohort of pregnant women admitted with COVID-19 in Cameroon, common presenting symptoms were fever, cough, and dyspnea; ultimately four of the 18 women died in hospital (case fatality rate: 22%). 18 Among the 13 women who delivered during the study, eight underwent cesarean section mostly because of maternal distress, and four newborns of the 13 deliveries died in hospital; however, neonatal outcomes could not be irrefutably attributed to COVID-19. 18 A second small-scale study from Senegal reported on nine pregnant women presenting largely with cough and rhinorrhea who were admitted; median time to recovery was ∼14 days, and none of them died.…”
mentioning
confidence: 93%
“… 18 Among the 13 women who delivered during the study, eight underwent cesarean section mostly because of maternal distress, and four newborns of the 13 deliveries died in hospital; however, neonatal outcomes could not be irrefutably attributed to COVID-19. 18 A second small-scale study from Senegal reported on nine pregnant women presenting largely with cough and rhinorrhea who were admitted; median time to recovery was ∼14 days, and none of them died. 19 Last, Nachega et al 20 described nearly 800 COVID-19 hospital admission cases from the Democratic Republic of the Congo, which included 12 pregnant women of a total of 262 women in the analysis.…”
mentioning
confidence: 93%